PERANAN LEMBAGA ADAT ACEH DALAM PENANGANAN KDRT DI KOTA LHOKSEUMAWE - Hidayat Hidayat; Budi Bahreisy; Muh. fahrudin Alawi (FISIP Universitas Malikussaleh, 2023)
Law of the Republic of Indonesia Number 23 of 2004 concerning the Elimination of Domestic Violence Article 1 defines domestic violence (KDRT) as: